The highly polarized open cluster Trumpler 27 - Feinstein Baigorri, Carlos (2000)
We have carried out multicolor linear polarimetry (UBVRI) of the brightest stars in the area of the open cluster Trumpler 27. Our data show a high level of polarization in the stellar light with a considerable dispersion, from P=4% to P=9.5%. The polarization vectors of the cluster members appear to be aligned. Foreground polarization was estimated from the data of some nonmember objects, for which two different components were resolved: the first one associated with a dust cloud close to the Sun producing Pλmax=1.3% and θ=146°, and a second component, the main source of polarization for the cluster members, originating in another dust cloud, which polarizes the light in the direction of θ=29.5d. From a detailed analysis, we found that the two components have associated values EB-V<0.45 for the first one and EB-V>0.75 for the other. Due the difference in the orientation of both polarization vectors, almost 90° (180° at the Stokes representation), the first cloud (θ~146°) depolarizes the light strongly polarized by the second one (θ~29.5d).